Exploring Side Effects of Warfarin in Outpatients at Tertiary Hospital in Indonesia - Fatimatuz Zahra Oviary Satryo; Dewi Wahyuni; Budi Suprapti; Wenny Putri Nilamsari; Mochamad Yusuf Alsagaff; Dewi Makmuroh Nurul Qomar Purnamawati; Bambang Subakti Zulkarnain (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2025)
Background: Patients with atrial fibrillation, venous thromboembolism, valvular disease, cardioembolic stroke, and acute myocardial infarction are prescribed the oral anticoagulant warfarin to treat thrombi. To guarantee its efficacy and safety, anticoagulants must be closely monitored. Furthermore, warfarin has a narrow therapeutic index, which increases the risk of side effects, particularly in the early stages of treatment. Objective: This study aimed to analyze the incidence of warfarin side effects in outpatients at Dr. Soetomo General Hospital. Methods: A retrospective cross-sectional design was adopted for outpatients at the Cardiology Department of Dr. Soetomo General Hospital from March to May 2023. Data were collected on the incidence of side effects in outpatients who received warfarin for a minimum of one month through an interview process. Other data, including age, sex, duration of warfarin therapy, comorbidities, and INR at the last scan, were extracted from medical records. The Chi-Square test was used to examine the data. Results: The results showed that 88 patients (42.7%) had side effects of bleeding (126 events). These included gum bleeding (22.3%), hematoma (20.4%), melena (7.7%), menometrorrhagia (2.4%), epistaxis (1.9%), hematuria (1.5%), hematemesis (1.0%), hemoptysis (1.0%), spontaneous venous bleeding  (1.0%), hematochezia (0.5%), hemostasis during blood sampling  (0.5%), tongue bleeding  (0.5%), and subconjunctival bleeding  (0.5%). Conclusion: The incidence of side effects during warfarin treatment was high, accounting for approximately 42.7% of cases. Furthermore, one patient experienced more than one side effect.